Standardization of Simplicia Golden Sea Cucumber (Stichopus hermanii) from Pelapis Island, West Kalimantan - Wintari Taurina; Mohamad Andrie (Majalah Obat Tradisional, 2022)
Standardization of medicinal ingredients and drug preparations is a requirement to ensure reproducibility of pharmaceutical and therapeutic quality. With standardization, it is hoped that it can further increase trust in medicines derived from natural ingredients. Golden sea cucumber is one of the natural ingredients that can be used as raw material for wound healing ointment preparations. The main content in golden sea cucumbers that play a role in wound healing is protein. This study aims to standardize the Simplicia of golden sea cucumber (Stichopus hermanii) originating from Pelapis Island, West Kalimantan. Standardization uses physical, chemical, and microbiological parameters like raw material requirements for standardized herbal medicines (OHT). The test is carried out in the laboratory using the method according to SNI. The results of the Simplicia test of golden sea cucumbers from Pelapis Island, West Kalimantan, included water content of 9.57%, zinc 9.32 mg/kg, cadmium < 0.030 mg/kg, copper < 0.030 mg/kg, lead < 0.066 mg/kg , mercury < 0.007 mg/kg, Total Plate Number 8.0 x 103 colonies/g, E.Coli < 3 APM/gr and Salmonella negative have fulfilled the requirements. The results of the Simplicia test of golden sea cucumbers include 13.4% ash content, 1.52% acid insoluble ash, 36.1% protein, 1.39% total fat, 13.1 mg/kg magnesium, and 10.6 mg iron. /kg. The results of the phytochemical screening of golden sea cucumber Simplicia were positive for containing alkaloids, saponins, and triterpenoids.